Notice of recent discoveries of Roman Remains at Cadder, on the Antonine Wall (Proceedings of the Society of Antiquaries of Scotland, 1854)
Mr Buchanan discusses a section of the Antonine wall near Glasgow where antiquarians expected to find a Roman fort. Traditionally, it was assumed that this fort was located somewhere near the parish church of Cadder, although there is no mention of the fort in Gordon's 1726 text on Roman sites. Buchanan suggests that this fort was located between the wall and the parish minister's manse, based evidence from Hamilton of Wishaw's publication (1710) and on recent finds in the area. He lists some of these finds including a Roman causeway, various pieces of pottery and nails. An inscribed stone tablet that the author believes may have belonged to the Second Legion Augusta and what may have been the garrison well were also uncovered.